Improving postgraduate supervision in an Open and Distance Learning (ODL) environment. A case study at the College of Education – University of South Africa (Unisa) - Heeralal, Prem Jotham (South African Journal of Higher Education, 2016)
In an open and distance learning (ODL) environment postgraduate students, in the main, study part time and are often far removed geographically from the university and their supervisors. There is very little face to face contact between the students and supervisors. Supervision takes place from a distance. Postgraduate students are not able to complete their qualifications in the minimum time required. The purpose of this paper is to examine how supervision of postgraduate students can be improved in an open and distance learning context so that students complete their qualification in the minimum time required. A qualitative approach was used to collect data from postgraduate ODL students. The results indicate that students are generally satisfied with the supervision that they receive, however, the following areas need to be considered in order to improve postgraduate supervision: proposal writing, research methodologies, data analysis, and the appropriate allocation of supervisors. The following recommendations are made: supervisors need to have more face to face contact with students, supervisors should be allocated to students on registration and regional workshops conducted by the university should specifically address the issues of proposal writing, research methodologies and data analysis.